Reconstrução de maxila severamente atrófica via enxerto ósseo autógeno de calota craniana: descrição de técnica - Pereira, Cassiano Costa Silva [UNESP]; Esper, Helen Ramon [UNESP]; Carvalho, Abrahão Cavalcante Gomes de Souza [UNESP]; Gaetti-Jardim, Ellen Cristina [UNESP]; Shinohara, Elio Hitoshio [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2012)
Bone reconstructions are traditionally conducted with autogenous grafts harvested from intra- or extra-oral donor sites to reestablish the lost bone volume for further implant-prosthetic rehabilitation. The calvarial bone has been studied as an excellent donor site in large atrophic situations, presenting low resorption rates, as well as complications and minimal morbidity. The hospitalization time is short, with low pain levels, short functional limitations, and invisible scars. The skull microarchitecture is predominantly cortical in the presence of growth factors that demonstrate their osteogenic, osteoinductive, and osteoconductive abilities resulting in low resorption rate and high predictability when compared to the iliac crest. Dural lacerations, extra and subdural bleeding, cerebrospinal fluid leakage, and brain damage have been minimized due to the development of surgical technique. The delimitation of diploe, preserving the internal skull cortex before osteotomy at the donor made it possible to reduce accidents and complications. The aim of this paper is to show a technical and to discuss aspects of the use of calvarial bone in the reconstruction of severely atrophic maxilla for oral rehabilitation with osseointegrated implants.

As reconstruções ósseas são tradicionalmente realizadas por meio de enxertos autógenos coletados de áreas doadoras intra e extrabucais, visando o restabelecimento do arcabouço perdido para posterior reabilitação implantoprotética. A calota craniana tem sido estudada como excelente opção em grandes atrofias, com baixa incidência de reabsorções, bem como de complicações e morbidade mínima. O tempo de hospitalização é curto, com baixo nível de dor, pequena limitação funcional e cicatriz imperceptível. A microarquitetura da calota craniana é predominantemente cortical com a presença de fatores de crescimento que evidenciam sua capacidade osteogênica, osteoindutora e osteocondutora acarretando baixa porcentagem de reabsorção e alta previsibilidade quando comparada a crista do ilíaco. Lacerações durais, hemorragias extra e subdurais, fístulas liquóricas e lesões cerebrais tem sido minimizadas em virtude do desenvolvimento da técnica cirúrgica. A delimitação da camada diploica, preservando a cortical interna do crânio, antes da realização das osteotomias no leito doador, possibilitou a diminuição de acidentes e complicações. O objetivo deste artigo foi apresentar nota técnica e discutir aspectos relativos à aplicação do osso de calota craniana na reconstrução de maxilas severamente atróficas, visando à reabilitação oral com implantes osseointegráveis.
Reconstruction of severely atrophic maxillary arch using calvarial autogenous bone graft: technical description
Keywords: Reconstructive procedures; Bone grafts; Calvarial; Surgical technique; Atrophic maxilla; Reconstrução; Enxerto ósseo; Calota craniana; Técnica cirúrgica; Maxila atrófica